2002
DOI: 10.1165/ajrcmb.26.6.4739
|View full text |Cite
|
Sign up to set email alerts
|

Polymers of α1-Antitrypsin Are Chemotactic for Human Neutrophils

Abstract: Plasma deficiency of alpha(1)-antitrypsin is most commonly due to the Z mutation ((342)Glu--> Lys) and is associated with early-onset panlobular emphysema. The lung disease in these patients is attributed to the relative deficiency of circulating alpha(1)-antitrypsin resulting in uncontrolled neutrophil-derived proteolytic activity. We have previously demonstrated that the local deficiency of Z alpha(1)-antitrypsin is exacerbated by the formation of polymers within the lung and now show that this polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(59 citation statements)
references
References 47 publications
0
59
0
Order By: Relevance
“…We have recently shown that circulating polymers of α 1 -antitrypsin are present in all individuals with ZZ α 1 -antitrypsin deficiency (mean 36.3+/-SD33.3µg/mL; n=517) and that the level is associated with COPD (OR 3.6, 95% CI 1.4-9.1) [45]. These observations provide a new paradigm for the pathogenesis of the emphysema associated with α 1 -antitrypsin deficiency -a combination of loss of anti-protease function combined with pro-inflammatory intrapulmonary polymers [44]. However it is still unknown whether the pro-inflammatory properties of polymers play an important role in the pathogenesis of the emphysema associated with α 1 -antitrypsin deficiency or whether the majority of the pathology is driven by the deficiency in the antiproteinase screen (Fig.…”
Section: Alpha 1 -Antitrypsin Polymers Inflammation and Emphysemamentioning
confidence: 79%
See 2 more Smart Citations
“…We have recently shown that circulating polymers of α 1 -antitrypsin are present in all individuals with ZZ α 1 -antitrypsin deficiency (mean 36.3+/-SD33.3µg/mL; n=517) and that the level is associated with COPD (OR 3.6, 95% CI 1.4-9.1) [45]. These observations provide a new paradigm for the pathogenesis of the emphysema associated with α 1 -antitrypsin deficiency -a combination of loss of anti-protease function combined with pro-inflammatory intrapulmonary polymers [44]. However it is still unknown whether the pro-inflammatory properties of polymers play an important role in the pathogenesis of the emphysema associated with α 1 -antitrypsin deficiency or whether the majority of the pathology is driven by the deficiency in the antiproteinase screen (Fig.…”
Section: Alpha 1 -Antitrypsin Polymers Inflammation and Emphysemamentioning
confidence: 79%
“…Polymers of α 1 -antitrypsin form within the lung as a result of local inflammation and exposure to cigarette smoke [39,40,42,43]. They are pro-inflammatory for human neutrophils in vitro [40,44] and in murine lungs in vivo [42]. Moreover cigarette smoke induces both intrapulmonary polymer formation and neutrophil influx in transgenic mice that express Z, but not M α 1 -antitrypsin [43].…”
Section: Alpha 1 -Antitrypsin Polymers Inflammation and Emphysemamentioning
confidence: 99%
See 1 more Smart Citation
“…This conformational transition may further reduce the levels of functional proteinase inhibitor in the lungs, and consequently exacerbate lung tissue damage (Elliott et al, 1998). Studies of Parmar et al (Parmar et al, 2002) and Mulgrew et al (Mulgrew et al, 2004) showed that Z A1AT locally produced on the epithelial surface of the lung polymerizes and A1AT polymers demonstrate proapoptotic and proinflammatory effects. These studies also revealed that unlike M A1AT protein, Z A1AT protein polymerized at body temperature, and in addition of being an ineffective antiprotease inhibitor, might become a strong neutrophil chemoattractant, thus representing an ongoing source of inflammation in the lungs of individuals with A1ATD.…”
Section: Z Variantmentioning
confidence: 99%
“…13 This conformational transition inactivates a 1 -antitrypsin as a proteinase inhibitor, thereby further reducing the already depleted levels of a 1 -antitrypsin that are available to protect the alveoli. (iii) Intrapulmonary polymers are chemotactic for human neutrophils in vitro, 14 and this may explain the finding that patients with Z a 1 -antitrypsin deficiency have an excess number of neutrophils in bronchoalveolar lavage 15 and in tissue sections of lung parenchyma. 6 The relative contribution of each of these pathways to lung damage in any given patient is unknown.…”
Section: Epidemiologymentioning
confidence: 99%